Lithuanian Syllable: The Hierarchy of Syllable Constituents and Syllable Weight - Kazlauskienė, Asta (Respectus Philologicus, 2022)
The article aims to establish the hierarchy of Lithuanian syllable constituents and determine how syllables should be interpreted in terms of syllable weight. The empirical data based on 311 000 syllables show that the variety of consonants in the onset is more significant than in the coda. A vowel and a succeeding approximant form the nucleus of a prosodic syllable, which shows strong coherency between a nucleus and a coda. Therefore, a CVC syllable is interpreted as [syllable Onset [rhyme Nucleus Coda]]. The division of Lithuanian syllables into light and heavy can be based on the realization of pitch accent, and it fully coincides with the traditional classification of long and short syllables in Lithuanian linguistics. Short syllables are light, their nucleus is a short vowel, and the number of consonants in the onset and the coda is unimportant. Such syllables account for almost half of all syllables in the database of this research (45%). Long syllables are heavy, and their nucleus may consist of long vowels (30%), diphthongs (12%), or mixed diphthongs (13%). When stressed, heavy syllables are pronounced in two ways: traditionally known as “acute” and “circumflex”. The stress is not dependent on the syllable weight, as both light (short) and heavy (long) syllables can be stressed. However, it has been observed that heavy (long) syllables are stressed more often than light (short) ones. Heavily stressed syllables constitute 25%, while light stressed syllables comprise 11% of all the syllables in this research database.
Keywords: syllable; nucleus; onset; coda; syllable-internal structure